2018
DOI: 10.1111/aas.13176
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of skin temperature during regional anaesthesia—What the anaesthesiologist should know

Abstract: Body temperature homeostasis is accurately regulated by complex feedback-driven neuronal mechanisms, which involve a multitude of thermoregulatory pathways. Thus, core temperature is constantly maintained within a narrow range. As one of the most effective regulatory systems skin temperature is dependent on skin blood flow. Skin blood flow in turn is highly dependent on sympathetic activity. Regional anaesthesia leads to blockade not only of somatosensory and motor nerve fibres but also of sympathetic fibres. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 78 publications
1
30
0
Order By: Relevance
“…The areas of cold hypoesthesia were tested using ice, which relies mainly on the patient's own judgment of cold rather than an objective judgment criterion. Indeed, changes in skin blood flow can be monitored by photoplethysmography or laser Doppler during a nerve block, which is a more reliable and sensitive technique than a subjective assessment of skin temperature changes (27). Second, the areas of cold hypoesthesia were tested at different time points after ESPB, but the area of sensory loss was not tested, and the recovery of postoperative sensation was not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…The areas of cold hypoesthesia were tested using ice, which relies mainly on the patient's own judgment of cold rather than an objective judgment criterion. Indeed, changes in skin blood flow can be monitored by photoplethysmography or laser Doppler during a nerve block, which is a more reliable and sensitive technique than a subjective assessment of skin temperature changes (27). Second, the areas of cold hypoesthesia were tested at different time points after ESPB, but the area of sensory loss was not tested, and the recovery of postoperative sensation was not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we only observed temperature fluctuations at the waist after taping. As a core region of the human body, the temperature of the waist is relatively high with little fluctuation, while the temperature of the distal extremities may be more susceptible to external intervention (Hermanns et al, 2018). Secondly, it has been reported that skin temperature distribution is influenced by the subcutaneous fat of each body segment.…”
Section: Limitationsmentioning
confidence: 99%
“…This type of temperature change can be detected by infrared thermography. Infrared thermography has been successfully applied in predicting the effectiveness of various regional blocks including upper and lower extremity block, epidural and spinal anesthesia [12]. However, its usefulness in TPVB has not been determined.…”
Section: Introductionmentioning
confidence: 99%